ATP and its metabolite adenosine as regulators of dendritic cell activity - Silva-Vilches, Cinthia; Ring, Sabine; Mahnke, Karsten (Frontiers in immunology, 2018)
Adenosine (Ado) is a well-studied neurotransmitter, but it also exerts profound immune regulatory functions. Ado can (i) actively be released by various cells into the tissue environment and can (ii) be produced through the degradation of extracellular ATP by the concerted action of CD39 and CD73. In this sequence of events, the ectoenzyme CD39 degrades ATP into ADP and AMP, respectively, and CD73 catalyzes the last step leading to the production of Ado. Extracellular ATP acts as a “danger” signal and stimulates immune responses, i.e. by inflammasome activation. Its degradation product Ado on the other hand acts rather anti-inflammatory, as it down regulates functions of dendritic cells (DCs) and dampens T cell activation and cytokine secretion. Thus, the balance of proinflammatory ATP and anti-inflammatory Ado that is regulated by CD39+/CD73+ immune cells, is important for decision making on whether tolerance or immunity ensues. DCs express both ectoenzymes, enabling them to produce Ado from extracellular ATP by activity of CD73 and CD39 and thus allow dampening of the proinflammatory activity of adjacent leukocytes in the tissue. On the other hand, as most DCs express at least one out of four so far known Ado receptors (AdoR), DC derived Ado can also act back onto the DCs in an autocrine manner. This leads to suppression of DC functions that are normally involved in stimulating immune responses. Moreover, ATP and Ado production thereof acts as “find me” signal that guides cellular interactions of leukocytes during immune responses. In this review we will state the means by which Ado producing DCs are able to suppress immune responses and how extracellular Ado conditions DCs for their tolerizing properties.